PENGARUH PEMBANGAN KARIR DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT ASURANSI JIWA ASTRA BUMI SERPONG DAMAI KOTA TANGERANG SELATAN - Pergiawan Listanto; Dede Sunaryo; Andi Kusumanegara (Universitas Muhammadiyah Bengkulu, 2025)
development and work discipline on employee performance at PT Asuransi Jiwa Astra. This study used a quantitative approach with a sample of 53 people. Data was obtained based on the distribution of questionnaires or questionnaires. Data processing using SPSS Version 29 software. The results of the study show that partially career development has a positive and significant influence on employee performance, shown by the tcal>ttable value (3.871>2.00758) significance value of 0.001 (0.001<0.05) and the regression coefficient has a positive value of 0.399. Work discipline partially has a positive and significant effect on employee performance, shown by the tcal>ttable value (2.851>2.00758) a significance value of 0.006 (0.006<0.05) and the regression coefficient has a positive value of 0.358. Simultaneously, career development and work discipline have a positive and significant effect on employee performance, shown by the value of F calculate>F table (499,987>2.79) and a significance of 0.001 (0.001<0.05).